Engineering materials and their applications - Flinn, Richard A. (Richard Aloysius), 1916-; Trojan, Paul K. (New York : J. Wiley, 1995)
This book is about: Fundamentals; Metals and alloys; Ceramic materials; Polymeric materials; Composite materials; ...
Keywords: Engineering; Materials; Materials